2019
DOI: 10.1016/j.drugalcdep.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The association between racial and socioeconomic discrimination and two stages of alcohol use in blacks

Abstract: Background: This study aimed to characterize the associations of racial and socioeconomic discrimination with timing of alcohol initiation and progression from initiation to problem drinking in Black youth. Methods: Data were drawn from a high-risk family study of alcohol use disorder. Mothers and their offspring (N=806; M age =17.87, SD age =3.91; 50% female) were assessed via telephone interview. Cox proportional hazards regression analyses were used to examine associations between discrimination and timing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 70 publications
(57 reference statements)
0
10
0
1
Order By: Relevance
“…Black youth are more likely to start drinking at a later age than their peers and consume less alcohol [ 5 , 9 ]. However, Black youth experience more negative social consequences from drinking, report more alcohol-related illnesses and injuries, and are less likely to recover from alcohol dependence when compared to White youth [ 2 , 10 , 11 ]. Although the rate of alcohol use is significantly lower among Black youth compared to other racial and ethnic groups, the rate of illicit drug use among them is higher [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Black youth are more likely to start drinking at a later age than their peers and consume less alcohol [ 5 , 9 ]. However, Black youth experience more negative social consequences from drinking, report more alcohol-related illnesses and injuries, and are less likely to recover from alcohol dependence when compared to White youth [ 2 , 10 , 11 ]. Although the rate of alcohol use is significantly lower among Black youth compared to other racial and ethnic groups, the rate of illicit drug use among them is higher [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outside of racial discrimination, general social discrimination has also been shown to promote college students’ drinking behavior in the United States [ 15 ]. For black Americans, both racial and socioeconomic discrimination increase their alcohol intake [ 16 ]. According to the stress-coping hypothesis, drinking behavior is an individual’s coping strategy to deal with social discrimination [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arshanapally, Werner, Sartor, and Bucholz (2017) found a link between racial discrimination and suicidality among AA males that is partially explained by maternal experience of racial discrimination. Another study of AA youth found that maternal experiences of discrimination protected against alcohol initiation among offspring, but this effect did not remain in fully adjusted models (Haeny et al, 2019). Both studies used data from the Missouri Family Study (MOFAM), which are also used in the current article (Arshanapally et al, 2017; Haeny et al, 2019).…”
Section: Parental Experiences Of Discriminationmentioning
confidence: 99%